2017
DOI: 10.1002/chem.201703005
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of Reactive Oxygen Species in an Artificial‐Enzyme‐Based Hollow Structure To Eliminate Adverse Effects of Photocatalysis on UV Filters

Abstract: Skin cancers caused by UV irradiation have been a major public health problem. One simple and effective way to avoid the above detrimental effects is the use of UV-protective sunscreens. However, there has been considerable concern with the issue of the production of reactive oxygen species (ROS) through the photodegradation of commercial UV filters. Herein, for the first time, it is reported that the integration of ZnO nanoparticles and CeO nanoparticles into hollow microspheres (ZnO/CeO HMS) could provide br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
(102 reference statements)
0
17
0
Order By: Relevance
“…Under the ultraviolet radiation, toxic reactive oxygen species are generated, leading to oxidative damage to the skin. To alleviate this problem, Qu and Ren’s groups introduced antioxidant nanozyme into the ZnO sunscreen agent . In their work, CeO x nanoparticles were chosen as the antioxidant enzyme models because of their excellent antioxidant activities.…”
Section: Recent Research Process Of Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the ultraviolet radiation, toxic reactive oxygen species are generated, leading to oxidative damage to the skin. To alleviate this problem, Qu and Ren’s groups introduced antioxidant nanozyme into the ZnO sunscreen agent . In their work, CeO x nanoparticles were chosen as the antioxidant enzyme models because of their excellent antioxidant activities.…”
Section: Recent Research Process Of Nanozymesmentioning
confidence: 99%
“…Nanozymes can also be used for sunscreens against UV damage. 655 It is well-known that long-term ultraviolet radiation can cause oxidative damage or even induce skin cancers in some cases. 656 For this reason, sunscreen is very important.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Also, we observed that NP encapsulation slowed UV filter degradation, possibly by creating an environment for poor stability in excited state. In addition, reduction of ROS upon UV irradiation by physical entrapment of UV filters has been demonstrated in ZnO/CeO x microspheres . Therefore, we hypothesized that our AVO/OCR‐NPs may also exhibit a similar reduction in free ROS.…”
Section: Resultsmentioning
confidence: 86%
“…For methods that use actives without covalent modification, solid NPs composed of various natural or synthetic materials can encapsulate the organic UV filters to slow down skin penetration of organic filters. NPs composed of silica, lipids, gelatin, and synthetic polymers encapsulating both organic and inorganic UV filters, have been reported, but only characterized in vitro. Previously, we explored the advantages of encapsulating an FDA approved organic UVB filter, padimate O (PO), into biodegradable polymeric NPs composed of amphiphilic co‐block polymer, poly( d , l ‐lactic acid)‐hyperbranched polyglycerol (PLA‐HPG).…”
Section: Introductionmentioning
confidence: 99%
“…[235] Likewise, "OR" and "XOR" logic gate operations have also been demonstrated by tuning catalase and oxidase-like activities of Au NPs with various metal ions. [236] Nanozymes have also been proved to have potential applications in UV protection, [237] antithrombosis therapy, [238] and bioorthogonal catalysis. [239] As discussed, artificial enzymes or nanozymes have received considerable attention in recent years owing to their potential applications in diverse fields of engineering and science.…”
Section: Applications and Opportunitiesmentioning
confidence: 99%